Seismic design of buildings to Eurocode 8 [ - Elghazouli, Ahmed Y. [ (Ahmed Youssef)] (Spon Press, 2009)
Covers seismic design and links the principles to the Eurocode 8 on the Design of Structures for Earthquake Resistance, illustrated with design examples. This book focuses on concrete and steel